Typological analysis of community participation for sustainable tourism in Sasak Ende Tourism Village - Arief Purnama Ajie; Lastiani Warih Wulandari; Isdarmanto Isdarmanto (Journal of Enterprise and Development (JED), 2024)
Purpose  — The purpose of this study is to analyze community participation in Sasak Ende Tourism Village in managing and designing sustainable tourism development strategies based on the results of typological analysis of community participation.Method — This study employs qualitative methods utilizing primary and secondary data sources. Data were gathered through observation, interviews, and documentation. We interviewed informants from the Central Lombok Tourism Office, the Managing Secretary of Sasak Ende Tourism Village, and Pujut Regency. Furthermore, triangulation analysis techniques were utilized in this study to assess the validity of the data.Result — Based on the analysis, three levels of community participation were identified in Sasak Ende Tourism Village: material incentive participation, interactive participation, and independent mobilization. Community participation activities in Sasak Ende Tourism Village adhere to socio-cultural, economic, and environmentally sustainable tourism principles. The strategy employed focuses on developing human resources (HR) and preserving Sasak traditional houses. The analysis results in a sustainable tourism development strategy for Sasak Ende Tourism Village based on the typology of participation and the principles of sustainable tourism.Practical implications — This study suggests that fostering various levels of community participation and aligning tourism development strategies with socio-cultural, economic, and environmental sustainability principles can lead to the preservation of cultural heritage and sustainable growth in destinations like Sasak Ende Tourism Village.